Hábitos de estudio en estudiantes de la facultad de odontología de la Universidad Antonio Nariño (2020)
Introduction: The academic performance of students depends on factors associated with study habits and attitudes, which are determinant for achieving academic success, according to it is important to conduct studies that allow understanding these variables. Objective: To identify the study habits of students in the Faculty of Dentistry at the Universidad Antonio Nariño. Materials and Methods: Study habits were evaluated according to the criteria of Picasso et al (1) and Salas (16), through the inventory of Gilbert Wrenn. This instrument differentiates between habits (behavior acquired through constant repetition, which has become stable and mechanical), and attitudes (behaviors that people use or adopt when faced with life or specific contexts). Results: Habits in the general work attitudes dimension showed the highest mean negative score and a smaller standard deviation than this one, therefore these habits were inadequate and likely to have an impact on academic performance; with respect to habits about reading and note-taking techniques, habits about time distribution and social relations during the study, habits about time distribution and social relations during the study were concluded to be neither adequate nor inadequate, therefore they do not affect the academic performance of the sampled population. Conclusions: the overall score achieved is low, which marks the existence of bad study habits associated with poor reading and note-taking techniques; bad habits used to concentrate on study activities and inadequate use of time, accompanied by inadequate work habits